2007
DOI: 10.1080/14697680601038167
|View full text |Cite
|
Sign up to set email alerts
|

Scenario-generation methods for an optimal public debt strategy

Abstract: We describe the methods employed for the generation of possible scenarios for term structure evolution. The problem originated as a request from the Italian Ministry of Economy and Finance to find an optimal strategy for the issuance of Public Debt securities. The basic idea is to split the evolution of each rate into two parts. The first component is driven by the evolution of the official rate (the European Central Bank official rate in the present case). The second component of each rate is represented by t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 18 publications
0
14
0
Order By: Relevance
“…Consequently, while Amadori's condition is verified, e.g., by the Bernaschi et al [9] model of correlated interest rate factors, it is not verified, e.g., by the Heston model (which, incidentally, does not satisfy the uniform Lipschitz assumption either). In addition, Amadori's condition rules out the possibility that the diffusion matrix a is identically zero in a direction orthogonal to the boundary, as is the case for Asian options.…”
Section: The Bates Model With Downward Jumps In the Volatilitymentioning
confidence: 94%
See 1 more Smart Citation
“…Consequently, while Amadori's condition is verified, e.g., by the Bernaschi et al [9] model of correlated interest rate factors, it is not verified, e.g., by the Heston model (which, incidentally, does not satisfy the uniform Lipschitz assumption either). In addition, Amadori's condition rules out the possibility that the diffusion matrix a is identically zero in a direction orthogonal to the boundary, as is the case for Asian options.…”
Section: The Bates Model With Downward Jumps In the Volatilitymentioning
confidence: 94%
“…Correlated interest rate factors Recently Bernaschi et al [9] proposed an n-factor term structure model for valuing public debt securities where each factor follows a CIR-type model, but the driving Brownian motions are correlated. Then the n-dimensional factor process is not affine.…”
Section: The Bates Model With Downward Jumps In the Volatilitymentioning
confidence: 99%
“…In Bernaschi et al (2007) is described a simulation model for the debt issuance, where the main economic risk factor is given by the interest rate. They adopt a mean reverting model for the term structure and link the fluctuations to a model for the official rate issued by the European Central Bank (ECB).…”
Section: Introductionmentioning
confidence: 99%
“…This model is illustrated using debt issuance data of the Italian government. Other notable work in this area includes Bernaschi et al (2007), which provides results on the multivariate simulation of interest rates using observable (ECB) rates as well as analysis of principal components. The research reported in Consiglio and Staino (2010) and Balibek and Köksalan (2010) is the closest in spirit to the work reported here, in the sense that, both these papers also develop multi-stage stochastic programming models for sovereign debt issuance.…”
Section: The Debt Management Problemmentioning
confidence: 99%
“…Bernaschi et al (2007)), we do not use macroeconomic variables to model the evolution of interest rates. Our supporting argument is that, the secondary sovereign debt market for OECD countries is quite liquid and reflects the view of the market participants about the evolution of macroeconomic variables.…”
Section: Y(t T ) = − 1 T − T P (T T ) = Log(a(t T )) − B(t T )R Tmentioning
confidence: 99%